2017
DOI: 10.1186/s12958-017-0303-0
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ superfamily signaling and uterine decidualization

Abstract: Decidualization is an intricate biological process where extensive morphological, functional, and genetic changes take place in endometrial stromal cells to support the development of an implanting blastocyst. Deficiencies in decidualization are associated with pregnancy complications and reproductive diseases. Decidualization is coordinately regulated by steroid hormones, growth factors, and molecular and epigenetic mechanisms. Transforming growth factor β (TGFβ) superfamily signaling regulates multifaceted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 112 publications
0
58
0
1
Order By: Relevance
“…TGFB1 , expressed in decidua and placenta in total RNA-seq, is a key upstream regulator in all cell types, confirming TGFβ1 is a significant coordinator of placental development at the maternal-fetal interface [34]. TGFB1 is specifically expressed in the EVT subcluster in trophoblasts which may coordinate invasion of EVTs with differentiation of STBs through its receptor TGFBR1 , which is expressed in both EVT and STB subclusters in our study (data not shown) and by others [27].…”
Section: Discussionmentioning
confidence: 99%
“…TGFB1 , expressed in decidua and placenta in total RNA-seq, is a key upstream regulator in all cell types, confirming TGFβ1 is a significant coordinator of placental development at the maternal-fetal interface [34]. TGFB1 is specifically expressed in the EVT subcluster in trophoblasts which may coordinate invasion of EVTs with differentiation of STBs through its receptor TGFBR1 , which is expressed in both EVT and STB subclusters in our study (data not shown) and by others [27].…”
Section: Discussionmentioning
confidence: 99%
“…Decidualization is a complex biological process, in which the endometrium undergoes extensive remodeling. ESCs undergo morphological, functional, and genetic changes to support embryo implantation and development . Previous studies have confirmed that CXCL16 is highly expressed in decidual tissue.…”
Section: The Role Of Cxcl16 In Normal Pregnancymentioning
confidence: 96%
“…TGF-β family proteins are also involved in ovulation, maternal-embryo interactions, embryonic development, such as gastrulation and morphogenesis, and uterine decidualization as well as regulation of male reproductive functions, e.g. testis development [14].…”
Section: Tgf -A Large Familymentioning
confidence: 99%
“…Mouse study shows that estradiol plays an important role in TGF-β1 activation in the uterus [23]. However, its role in decidualization in humans remains unclear; several studies have shown that it acts as an inhibitor of decidualization, decreasing PRL, IGFBP-1 and TF expression [14]. However, other findings suggest that TGF-β1 secreted by endometrial epithelial cells reinforces decidualization and is highly expressed in its active form during this process [23].…”
Section: Transforming Growth Factor Betamentioning
confidence: 99%
See 1 more Smart Citation